Antiulcerogenic activity of species Annona coriacea Mart. and Spiranthera odoratissima A. St. Hil - Fernanda Neves Estrela; Keise Rodrigues Silva; Álefe Cardoso Cruz; Patrícia Fernandes de Souza; Leonardo Oliveira Costa; João Gabriel Moraes Junqueira; Geraldo Sadoyama Leal; Lucia de Paula; Helder Nagai Consolaro; Ana Paula Terezan; Vanessa Gisele Pasqualotto Severino; Anderson Luiz- Ferreira (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Background: Medicinal plants from the Brazilian Cerrado are used in folk medicine to treat several diseases such as gastric disorders. Purpose: The present work evaluated the antiulcerogenic and antimicrobial effects of the ethanolic extracts obtained from leaves of two Cerrado plant species. Methods: The action of ethanolic extracts of Spiranthera odoratissima (SOL) and Annona coriacea (ACL) were evaluated in experimental in vivo models in rats that simulated this disease in human gastric mucosa. Additionally, a pharmacological study to test antimicrobial activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were also evaluated by microdilution methods. Results: The pretreated with SOL (100, 200 and 300 mg/kg, p.o.) promoted signifi cant inhibition of mucosal injury (93, 99 and 98% inhibition; respectively). This inhibition also was detected in ACL treatment (50, 100, 200 and 300 mg/kg; 67, 52, 48 and 67% inhibition, respectively). The both extracts SOL (100 mg/ kg) and ACL (50 mg/kg) also reduced signifi cantly the formation of gastric lesions induced by indomethacin (73 and 63%, respectively) when compared to animals treated with respective vehicle. The phytochemical profi le from SOL and ACL indicated the presence alkaloids as a main constituent of these extracts. ACL but not displayed antimicrobial activities in vitro. Conclusion: Spiranthera odoratissima and Annona coriacea species present gastroprotective activity, supporting previous claims that its traditional use can treat gastrointestinal disorders.